Greek colonisation.
1 online resource (lxxxiv, 546 pages)
Keywords: The 2-volume handbook is dedicated to one of the most significant processes in the history of ancient Greece - colonisation. Greeks set up colonies and other settlements in new environments, establishing themselves in lands stretching from the Iberian Peninsula in the west to North Africa in the south and the Black Sea in the north east. In this colonial world Greek and local structures met, influenced and enriched each other. The handbook brings together historians and archaeologists, all world experts, to present the latest ideas and evidence. The principal aim is to present and update the general picture of this phenomenon, showing its importance in the history of the whole ancient world, including the Near East. The work is dedicated to Prof. A.J. Graham. This first volume gives a lengthy introduction to the problem, including methodological and theoretical issues. The chapters cover Mycenaean expansion, Phoenician and Phocaean colonisation, Greeks in the western Mediterranean, Syria, Egypt and southern Anatolia, et cetera The volume is richly illustrated.